2017
DOI: 10.1037/apl0000248
|View full text |Cite
|
Sign up to set email alerts
|

Employee conscientiousness, agreeableness, and supervisor justice rule compliance: A three-study investigation.

Abstract: Researchers have paid limited attention to what makes organizational authority figures decide to treat their employees either justly or unjustly. Drawing from the actor-focused model of justice, as well as the stereotype content model, we argue that employee conscientiousness and agreeableness can impact the extent to which supervisors adhere to normative rules for distributive, procedural, informational, and interpersonal justice, as a result of supervisors' evaluations of their employees' effort and their li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 99 publications
2
19
0
2
Order By: Relevance
“…The present results suggest that employees' attitudes and behaviors are shaped by factors other than the supervisor's enacted justice in regard to pay setting (i.e., insofar as the ratings of enacted justice reflect their actual behavior in relation to pay setting). Even though the supervisors' behaviors have previously been found to impact employees' attitudes and behavior (Karam et al, 2019), the present results are in line with studies indicating that employees do not passively receive justice from their supervisors (Zapata et al, 2013;Huang et al, 2017;Karam et al, 2019). Along with supervisors having been identified as having a key role in employees' justice perceptions, it has also been pointed out that supervisors' enacted justice can act as an antecedent to employees' perceived justice (Koopman et al, 2019) and that employees shape their justice perceptions based on their supervisors' actions.…”
Section: Effects Of Enacted Pay Justicesupporting
confidence: 91%
See 3 more Smart Citations
“…The present results suggest that employees' attitudes and behaviors are shaped by factors other than the supervisor's enacted justice in regard to pay setting (i.e., insofar as the ratings of enacted justice reflect their actual behavior in relation to pay setting). Even though the supervisors' behaviors have previously been found to impact employees' attitudes and behavior (Karam et al, 2019), the present results are in line with studies indicating that employees do not passively receive justice from their supervisors (Zapata et al, 2013;Huang et al, 2017;Karam et al, 2019). Along with supervisors having been identified as having a key role in employees' justice perceptions, it has also been pointed out that supervisors' enacted justice can act as an antecedent to employees' perceived justice (Koopman et al, 2019) and that employees shape their justice perceptions based on their supervisors' actions.…”
Section: Effects Of Enacted Pay Justicesupporting
confidence: 91%
“…However, even on a correlational level, no significant relationship was found in our study between the perceived justice ratings of the employees and the enacted justice ratings of the supervisors. In the few previous studies on justice that have measured both perceived and enacted justice, however, weak but significant correlations have been found between the two (Zapata et al, 2013;Huang et al, 2017;Koopman et al, 2019). For instance, Koopman et al (2019) found a 0.33 correlation between overall justice perceptions and overall justice enactment.…”
Section: Effects Of Enacted Pay Justicementioning
confidence: 94%
See 2 more Smart Citations
“…As an example, Huang et al. () examined how higher conscientiousness and agreeableness in employees may elicit supervisors to perceive higher levels of employee effort and greater degrees of interpersonal liking, which, in turn, lead to supervisors’ greater compliance with justice rules when interacting with these employees. Similarly, we posit that high conscientiousness and high GMA may elicit more favorable reactions from supervisors, allowing supervisors to offer customized work arrangements (idiosyncratic deals; Liao, Wayne, & Rousseau, ).…”
Section: Discussionmentioning
confidence: 99%